T-Cell Exhaustion in Mycobacterium tuberculosis and Nontuberculous Mycobacteria Infection: Pathophysiology and Therapeutic Perspectives - Lombardi, Andrea; Villa, Simone; Castelli, Valeria; Bandera, Alessandra; Gori, Andrea (Microorganisms (Basel), 2021)
Immune exhaustion is a condition associated with chronic infections and cancers, characterized by the inability of antigen-specific T cells to eliminate the cognate antigen. Exhausted T cells display a peculiar phenotypic profile and exclusive functional characteristics. Immune exhaustion has been described in patients with Mycobacterium tuberculosis infection, and cases of tuberculosis reactivation have been reported in those treated with immune checkpoint inhibitors, drugs able to re-establish T-cells’ function. Exhausted T CD8+ cells’ profile has also been described in patients with infection due to nontuberculous mycobacteria. In this review, we initially provide an overview of the mechanisms leading to immune exhaustion in patients infected by Mycobacterium tuberculosis and nontuberculous mycobacteria. We then dissect the therapeutic perspectives related to immune checkpoint blockade in patients with these infections.